THE EFFECT OF CO-PROCESSED EXCIPIENTS DURING FORMULATION AND EVALUATION OF PEDIARIC LEVETIRACETAM ORODISPERSIBLE TABLETS IN RATS - TEAIMA, MAHMOUD H.; EL MESSIRY, HUSSIEN MOHAMED AHMED; DAHI OSMAN, TASNEEM; A. EL-NABARAWI, MOHAMED; A. HELAL, DOAA (International Journal of Applied Pharmaceutics, 2023)
Objective: The main aim of this research was to make cost-effective taste-masking oral pediatric orodispersible tablets (ODTs) of Levetiracetam as an antiepileptic drug (AED) using various co-processed excipients by direct compression method. Methods: Eight kinds of ready-made co-processed excipients in addition to sucralose and menthol as a sweetener, were utilized. The weight variation, drug content, friability, in vitro disintegration, dissolution time, hardness, thickness, and pharmacokinetics of the produced ODTs were determined. Results: The optimized formula (F5) containing Pharmaburst® 500 showed the shortest disintegration time (11.66 sec) and more than 98% of Levetiracetam within 10 min (Q10). The Pharmacokinetic study of this optimum formula (F5) in rats using an HPLC-UV detector showed 26.904±2.027 ng/ml as the Cmax and 101.935±0.894 h ng/ml as AUC compared to commercial Tiratam® solution 10.421±0.295ng/ml and 23.135±0.43 h ng/ml respectively. Conclusion: Levetiracetam orally orodispersible tablets were successfully prepared with acceptable hardness, satisfactory taste, and rapid disintegration in the oral cavity avoiding first-pass metabolism to yield the desired rapid effect in facing epilepsy for patients who experience dysphagia like pediatric and geriatric. In addition to the unconsciousness of the epileptic patient followed the seizure attack.